2021
DOI: 10.1002/jsfa.11300
|View full text |Cite
|
Sign up to set email alerts
|

Effects of climate change and crop management on changes in rice phenology in China from 1981 to 2010

Abstract: BACKGROUND: Crop phenology change is co-determined by climate change and adaptation strategies, such as crop management, but their combined and isolated impacts on rice phenology are still unclear. Quantifying the impacts and identifying the main contributors are critical to food security under climate change. Thus we distinguished and quantified the relative contribution of climate change and crop management to rice (Oryza sativa L.) phenological changes in China from 1981 to 2010, using a first-difference mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…The response of vegetation change to climatic factors can be estimated using a multiple regression model [48], as shown in Equation ( 7):…”
Section: Relative Contribution Analysismentioning
confidence: 99%
“…The response of vegetation change to climatic factors can be estimated using a multiple regression model [48], as shown in Equation ( 7):…”
Section: Relative Contribution Analysismentioning
confidence: 99%
“…Observed rice phenology data recorded by agrometeorological stations from 1981 to 2018 were obtained from the CMA. The data set has been widely used and recognized as a high‐quality observation data set in China (Chen et al., 2021; L. Zhang, Zhang, Tao, et al., 2022; Tao et al., 2013). Observations were recorded by professional staff at two‐day intervals following the specifications for agrometeorological observation—Rice (QX/T 468–2018).…”
Section: Methodsmentioning
confidence: 99%
“…A similar focus on concurrent precipitation extremes was also mentioned concerning crop yield, as concurrent extremes could cause larger impacts than individual extremes (Feng et al, 2019;. Such high-impact modulation effects of concurrent precipitation extremes are currently ignored by agriculture risk management using empirical statistical models, which mostly rely on future temperature sensitivity (Liu, Zhang, et al, 2021), and process-based models, whose structure excluded the potential influence of such modulation effects (Zhang & Tao, 2019). Additionally, current widely accepted adaptation measures only based on the response to temperature, such as adjusting sowing date and breeding long growth period cultivar, need to reappraise their robustness for this underappreciated risk on agriculture production and for better adapting to climate change (Ding et al, 2020;.…”
Section: Rice Transplanting Date Responses To Temperature Extremes An...mentioning
confidence: 98%
See 1 more Smart Citation
“…For example, rising temperatures shortened the GP for early rice, prolonged the GP for late rice, and had less impact on the GP for single rice in China [35][36][37]. Chen et al [38] incorporated temperature, precipitation, and sunshine hours into a linear regression model to estimate the phenology response in China. He found that the maximum positive sensitivity came from the sunshine hour and the maximum negative sensitivity was from temperature.…”
Section: Improvements In Identifying Climate Contributions On Rice Ca...mentioning
confidence: 99%